The Effect of Governance, Public Participation, and Public Health Expenditure on Public Health Outcome in Thailand - Chinatthaporn, Natthachai; Sahapattana, Prapon (Journal of Politics and Governance, 2024)
The objective of this study is to examine the effect of governance, public participation, and public health expenditure on public health outcomes in Thailand. Additionally, the study aims to offer policy suggestions for enhancing public health outcome in Thailand. The study was conducted using a quantitative methodology, making use of an extensive database that covered the period from 2009 to 2020. The key findings suggested that the participation of the public plays a significant role in enhancing health outcomes. The active participation of community members plays a crucial role in enhancing health outcomes throughout the various provinces of Thailand. Furthermore, enhancing health outcomes depends on effective governance. The impact of government effectiveness, corruption control, and accountability on public health outcomes is considerable. Public health outcomes are explained by governance, as determined by provincial tax collection and government action complaints regarding corruption. The determinant of public health expenditures has been found to have a statistically significant impact on public health outcomes, albeit with a relatively modest effect size. The findings for policy recommendations for improving public health outcomes in Thailand provinces indicated that policymakers should consider the promotion of community participation and the improvement of governance, with a particular emphasis on government effectiveness, accountability, and corruption control dimensions, as additional measures to improve public health outcomes.